Pengaruh Penggunaan Onggok dan Ampas Tahu Terfermentasi Mix Culture (Aspergillus niger dan Rhizopus oligosporus) Sebagai Pengganti Jagung Dalam Pakan Terhadap Kualitas Fisik Daging Ayam Pedaging (Faculty of Animal Science Universitas Brawijaya, 2015)
The experiment was conducted to evaluate physical quality of meat in broiler fed diets with addition of tapioca by-product and tofu waste fermented with a combination Aspergillus niger and Rhizopus oligosporus as a substitution for corn. Two hundred DOCâ€™s unsex Lohmann Platinum strain were randomly divided into 25 groups containing eight birds each. Experiment was designed by using â€œCompletely Randomized Designâ€ with five treatments, replicated five times. The treatments of feed used were P0 = basal diet + corn P1 = basal diet + Corn subtituted 5% OAF, P2 = basal diet + Corn subtituted 10% OAF, P3 = basal diet + Corn subtituted 15% OAF, P4 = basal diet + Corn subtituted 20% OAF. Chickens were raised for 35 days. Drinking water and feed were given ad libitum. Meat samples (Pectoralis superficialis) were taken to determine the physical qualities of meat. The results showed that addition of OAF did not exertisignificant effect on carcass presentage, pH, water-holding capacity, and cooking loss of meat of broiler. The conclusion was that the additional of OAF cannot improve the quality of physical broiler meat. The best result showed at third treatment with 15% OAF substitution of feed.